4.2k views
1 vote
How do you do this?!
(2w-1)/(4)=(2-w)

2 Answers

5 votes

Answer:


w = (3)/(2)

Explanation:

Let's solve:


(2w - 1)/(4) =2−w

Step 1: Simplify both sides of the equation.


(2w - 1)/(4) =2−w \\ (1)/(2) w+ ( - 1)/(4) =2+−w(Distribute) \\ (1)/(2) w+ ( - 1)/(4) =−w+2

Step 2: Add w to both sides.


(1)/(2) w+ ( - 1)/(4) +w=−w+2+w\\ (3)/(2) w+ ( - 1)/(4) =2

Step 3: Add 1/4 to both sides.


(3)/(2) w+ ( - 1)/(4) + (1)/(4) =2+ (1)/(4) \\ (3)/(2) w= (9)/(4)

Step 4: Multiply both sides by 2/3.


( (2)/(3) )*( (3)/(2) w)=( (2)/(3) )*( (9)/(4) )

Therefore, the answer will be w = 3/2.

User Alexglue
by
5.3k points
3 votes

Answer:

w = 3 is your answer.

Explanation:

You want to get w by itself.

(2w - 1)/(4) = 2 - w You will add the w on both sides.

(3w - 1)/(4) = 2 You will multiply 4 on both sides.

3w - 1 = 8 You will add 1 on both sides.

3w = 9 You will divide 3 on both sides.

w = 3 is your answer.

User BlueFrog
by
5.4k points